Present status of naturally occurring seaweed flora and their utilization in Bangladesh - Sarkar, Md Shirajul Islam; Kamal, Md; Hasan, Muhammad Mehedi; Hossain, Md Ismail (Research in Agriculture Livestock and Fisheries, 2016)
A survey was conducted to know the present status of naturally occurring seaweed flora and their utilization in Bangladesh by interviews of scientific officers of MFTS (Marine Fisheries and Technology Station, Bangladesh Fisheries Research Institute, Coxs Bazar), NGO officials associated with seaweed research project, local seaweed food products manufacturer, seaweed collectors and Mog or Rakhyine tribal community of Coxs Bazar and St. Martin Island. Lack of knowledge on availability, distribution, seasonal variation, utilization status is causing impediment on utilization (e.g. seaweeds as human food, hydrocolloids, animal feed, fertilizer, cosmetic products, etc.) of available seaweeds naturally occurring in Bangladesh. Seaweeds are available along the whole Bangladeshi coast, mostly in St. Martin Island, Coxs Bazar and Sundarbans Mangrove forest. Total 193seaweed species including 19 commercially important species, belonging to 94 genera are found. Approximately, 5,000 metric ton of seaweed biomass is available. Due to seasonal variation in water quality parameters, generally seaweeds are available from October to April, but highest abundance occurs from January to March. Seaweed salad and sauce has been utilizing by Mog people as food. About 400 seaweed collectors at St. Martin Island annually harvested 6-9 metric tons of wet seaweeds (Hypnea spp.) for smuggling to Myanmar. Different value added food, functional food and personal care products have prepared by Govt. institution, NGO and in private sector. Considering the economic importance and potentials of seaweeds, for effective and environmentally sustainable utilization, special concern is required by both government and private organizations. Res. Agric., Livest. Fish.3(1): 203-216, April 2016